P0222KIDNEY EFFECTS IN THE MOXIE TRIAL: A STUDY OF OMAVELOXOLONE IN PATIENTS WITH FRIEDRICH'S ATAXIA. (6th June 2020) - Zaoui, Philippe; Chin, Melanie; Delatycki, Martin; Giunti, Paola; Goldsberry, Angie; Meyer, Colin; O'Grady, Megan; Perlman, Susan; Subramony, S H; Zesiewicz, Theresa; Lynch, David
Abstract: Background and Aims: Omaveloxolone, an Nrf2 activator, is an investigational drug that targets targets inflammation and mitochondrial dysfunction, metabolic, and bioenergetic pathways. Omaveloxolone is an analog of bardoxolone, methyl which has been shown to improve kidney function in multiple studies of chronic kidney diseases. The MOXIe Part 2 trial investigated omaveloxolone in patients with Friedreich's ataxia (FA), a rare and serious hereditary disease caused by mitochondrial dysfunction that affects multiple organ systems resulting in ataxia, cardiomyopathy, and reduced lifespan. The study met its primary efficacy endpoint, and omaveloxolone improved neurological function, as assessed by the modified Friedreich's ataxia rating scale (mFARS). We report the effect of omaveloxolone on kidney function in this patient population. Method: The MOXIe trial (NCT02255435) was an international, multi-center, double-blind, placebo-controlled, randomized trial that enrolled 103 patients between 16 and 40 years of age with genetically confirmed FA. Patients were randomized 1:1 to receive either omaveloxolone 150 mg or placebo administered once daily for 48 weeks. The trial included 24 patients that were younger than 18 years of age. Baseline eGFR for the overall patient population receiving placebo or omaveloxolone was 109.2 ± 21.7 and 113.4 ± 14.7 mL/min/1.73 m2, respectively. Baseline eGFR for the pediatric population receiving placebo or omaveloxolone was 99.1 ± 33.7 and 106.3 ± 15.6 mL/min/1.73 m2, respectively. Serum creatinine was collected at baseline, Weeks 4, 12, 18, 24, 36 and 48 on-treatment and 4-weeks off-treatment at Week 52. Glomerular filtration rate was estimated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation for patients ≥ 18 years of age. For patients <18 years of age, the Bedside Schwartz equation was used to calculate eGFR. Results: In placebo patients, mean (SD) eGFR decreased by 4.4 ± 11.0 mL/min/1.73 m2 from baseline whereas patients receiving omaveloxolone had an average increase of +7.0 ± 10.7 mL/min/1.73 m2 from baseline after 48 weeks, resulting in a difference of 11.4 mL/min/1.73 m2 between treatment groups. At Week 52, mean eGFR was -4.2 ± 10.9 mL/min/1.73 m2 relative to baseline in placebo patients and remained +0.9 ± 10.8 mL/min/1.73 m2 above baseline in omaveloxolone patients after 4-weeks off-treatment. In pediatric patients randomized to placebo, at week 48 eGFR decreased by -11.3 ± 14.3 mL/min/1.73 m2 whereas patients receiving omaveloxolone had an average increase of +5.5 ± 14.5 mL/min/1.73 m2 from baseline, resulting in a difference of 16.8 mL/min/1.73 m2 between treatment groups. Conclusion: Patients with FA randomized to placebo in the MOXIe trial had eGFR declines over 48 weeks that were similar to rates of decline observed in the most rapidly progressing forms of chronic kidney disease. The rapid kidney function decline in FA reflects the multi-system nature of the disease whereby mitochondrial dysfunction, and associated chronic inflammation, affects not only the central nervous system but also the heart and possibly the kidney. In contrast to placebo, treatment with omaveloxolone improved eGFR in patients with FA and the effects were sustained through one year of treatment. The durability of eGFR improvements are consistent with those observed with its analog, bardoxolone methyl, in clinical trials for various forms of CKD.